The Design of Off-grid Home Photovoltaic Power Generation System Considering Multi-weather Conditions. (May 2020) - Yu, Haixin; Liu, Dengfeng
Abstract: In the traditional fixed-installed off-grid photovoltaic power generation system, there are disadvantages such as insufficient solar energy collection and low solar energy utilization. In order to be able to effectively develop and utilize solar energy, the method of solar position tracking is generally used. In this paper, a single-chip microcomputer is selected as the main control chip, and a photovoltaic power generation system that combines two methods of photoelectric tracking and computational solar tracking and takes into account various meteorological factors is realized. The latitude and longitude information and time information collected by the single-chip microcomputer are used to calculate the sun position, and the photoelectric position is used to monitor the sun position. The design can automatically change the tracking scheme according to the weather conditions, so that the tracking system can run stably under various weather conditions.